2019
DOI: 10.1111/acem.13673
|View full text |Cite
|
Sign up to set email alerts
|

Study Enrollment When “Preconsent” Is Utilized for a Randomized Clinical Trial of Two Treatments for Acute Agitation in the Emergency Department

Abstract: Background: Acute agitation in the emergency department (ED) represents a danger to both patients and their caregivers. Medication is often needed, and few high-quality randomized trials have evaluated the optimal drugs for this vulnerable population. In the United States, as of 2017, randomized trials of drugs typically cannot be conducted under Waiver of Consent (46 CFR 45.116), and Exception From Informed Consent trials (21 CFR 50.24) are limited to life-threatening conditions, are onerous, and require fili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…Two of the articles were commentaries 24 25 ; one was a consensus statement 26 ; one consisted of semistructured interviews 27 ; one was a historical review 28 ; and one was a cohort study. 29 Specific conditions addressed included acute psychiatric illnesses (n=2), 24 29 pneumonia (n=1) 27 and stroke (n=1). 25 Two articles did not mention specific conditions 26 28 but rather addressed emergency conditions in general.…”
Section: Resultsmentioning
confidence: 99%
“…Two of the articles were commentaries 24 25 ; one was a consensus statement 26 ; one consisted of semistructured interviews 27 ; one was a historical review 28 ; and one was a cohort study. 29 Specific conditions addressed included acute psychiatric illnesses (n=2), 24 29 pneumonia (n=1) 27 and stroke (n=1). 25 Two articles did not mention specific conditions 26 28 but rather addressed emergency conditions in general.…”
Section: Resultsmentioning
confidence: 99%
“…We studied whether agitated patients had capacity to consent, using a standardized capacity tool 5 ; whether legally authorized representative consent was feasible 4 ; and whether obtaining "preconsent" (rather than prospective consent) could be used. 6 The findings from these studies all clearly demonstrated that meaningful informed consent is not practical or ethical in this population, and that these alternative consent methods are also not plausible.…”
Section: In Replymentioning
confidence: 87%
“…We sought to enroll them ahead of time in an RCT that would compare two treatment regimens, should they have a future visit for acute agitation; this approach was suggested by the FDA. When this methodology was used, we screened 1,461 patients and were unable to enroll a single patient via “preconsent.” 51 Even if enough resources were available to utilize LARs, preconsent, and consent tools each to maximum capacity, the resulting study would likely contain highly biased data. As such, it is likely a waiver or EFIC will be needed to obtain high‐quality data to inform practice and improve care for these patients.…”
Section: Discussionmentioning
confidence: 99%